Effect of Positivism in Clinical Legal Education - Samekto, Adji (The Indonesian Journal of International Clinical Legal Education, 2019)
Clinical Legal Education (CLE) is an education in legal study that aims toprovide knowledge on practical expertise that aims to make lawgraduates capable of providing legal services (legal advocacy).CLEbecome important in recent days because of the tendency to resolvethe matter through legal channels is increasing. But in fact, it showsthat law enforcement is almost interpreted only as rule enforcement.The trend that happens, aspects of compliance procedures takeprecedence over justice. The modern law scientification is stronglyinfluenced by the emergence of positivism paradigm in modernscience. At present, along with the complexity of the problems ofpeople and society, the main character of modern law is a rationalnature. Rationality is characterized by the nature of a procedural rule oflaw. Procedure, thereby becoming an important legal basis to establishwhat is called justice, even the procedure becomes more importantthan talking about justice itself. Legal education, thus more likely toproduce professional practitioners. The resulting legal practitioners arelegal actors who are expected to make a decision which side is wrongand what is right under the provisions of the law. Through this paper isexpected to obtain the understanding that CLE should not result theLaw degree who only give priority to the compliance procedure aspositive law, but also still guided ethics and efforts to achieve justice.The method used for writing this paper is the socio legal research withinductive analysis. Thus, the fact that occurred in the law enforcementpractices will be a major premise and provide input and analysis in thispaper.